PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SARANA KALTIM VENTURA - Eni Hidayanti (OBOR: Oikonomia Borneo, 2019)
This study aims to examine and analyze the effect of work motivation and work discipline on job satisfaction of employees of PT. Facilities Kaltim Venture. This study uses a descriptive methodology with a quantitative approach. The sample in this study were all 33 employees. The data was collected by using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression with the following test results: Y = 2.114 + 0.624X1 + 0.265X2.Th e results of this study indicate that there is a positive and significant influence between work motivation and work discipline on job satisfaction of employees of PT. Facilities Kaltim Venture. Partially, work motivation has a positive and significant effect on job satisfaction with tcount of 6.125 > ttable 2.042 with sig value of 0.000 <0.05. And work discipline has a positive and significant effect on job satisfaction with tcount of 2.485 > ttable 2.042 with a sig value of 0.019 <0.05